Tumor counterattack: fact or fiction? - Igney, Frederik; Krammer, Peter H. (Cancer immunology immunotherapy, 2005)
Cancer development relies on a variety of mechanisms that facilitate tumor growth despite the presence of a functioning immune system. Understanding these mechanisms may foster novel therapeutic approaches for oncology and organ transplantation. By expression of the apoptosis-inducing protein CD95L (FasL, APO-1L, CD178), tumors may eliminate tumor-infiltrating lymphocytes and suppress anti-tumor immune responses, a phenomenon called “tumor counterattack”. On the one hand, preliminary evidence of tumor counterattack in human tumors exists, and CD95L expression can prevent T-cell responses in vitro. On the other hand, CD95L-expressing tumors are rapidly rejected and induce inflammation in mice. Here, we summarize and discuss the consequences of CD95L expression of tumor cells and its contribution to immune escape.
This article is a symposium paper from the conference ‘‘Tumor Escape and Its Determinants’’, held in Salzburg, Austria, on 10–13 October 2004
Gesehen am 02.03.2021